The Implementation of Suggestopedia in EFL Classroom: How Does Music Improve Learners' Motivation In Language Learning? - Sepyanda, Marsika; Zainil, Yetti; Syarif, Hermawati; Zaim, M. (Proceedings International Conference on Education Innovation and Social Science, 2023)
Providing the learners with a comfortable and relaxing environment is a thing that should be considered by the teachers in order to improve the learners’ motivation in learning English as foreign language. This study aimed to explore about how the use of music as a part of Suggestopedia approach can improve learners’ motivation in language learning. It observed an EFL class that use Suggestopedia in teaching and learning process. The result showed that Suggestopedia was used by giving a comfortable and relaxed condition of the classroom for the learners. The lecturers also use selected music to make the situation of the class become relax and calm. Most of the learners also looked enjoyed the learning process and they focused on activities done in the classroom. In other words, music used in Suggestopedia can improve their motivation in language learning Therefore, suggestopedia is considered as an approach that can help to reduce learners' anxiety and stress levels in teaching and learning process.